Intramembrane proteolysis in regulated protein trafficking - Lemberg, Marius (Traffic, 2011)
Regulated intramembrane proteolysis is an evolutionarily conserved mechanism by which membrane-anchored bioactive molecules are released from cellular membranes. In eukaryotic cells, intramembrane proteases are found in different cellular organelles ranging from the endosomal system to mitochondria and chloroplasts. These proteases function in diverse processes such as transcription control, regulated growth factor secretion and recently even a role in the control of mitophagy has been suggested. Genomic annotation has predicted 13 different intramembrane proteases in humans. Apart from few studied examples, very little is known about their function. This review describes emerging principles of how intramembrane proteases contribute to the regulation of cellular protein trafficking in eukaryotic cells and raises the important question of how their activity is controlled.
Gesehen am 15.08.2022